2015
DOI: 10.1007/s11090-015-9637-6
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Argon–Nitrogen Atmospheric Pressure DC Arc Plasma

Abstract: The effect of nitrogen addition (1-20 %) on atmospheric argon DC arc plasma parameters was investigated. Nitrogen was added to three initial plasma gas compositions: pure argon gas, argon gas with water aerosol, and argon gas with water aerosol containing 0.5 % KCl. Admixtures of nitrogen from 1 up to 10 % (in the case of Ar-N 2 -water aerosol plasma) or up to 5 % (in the presence of 0.5 % KCl) produced a more contracted discharge, with larger gradients of electron number density and temperature, as compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 38 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…We found that the I G /I 2D ratio for samples A and B were 3.53 and 3.04, respectively, which corresponded to the multilayer graphene [44,45]. The addition of N 2 gas with Ar improved the thermal conductivity of the mixed plasma and increased the number of molecular ions [46]. The improved thermal and electrical conductivity of the nitrogen provided better nucleation conditions and, hence, more graphene layers were obtained.…”
Section: Resultsmentioning
confidence: 87%
“…We found that the I G /I 2D ratio for samples A and B were 3.53 and 3.04, respectively, which corresponded to the multilayer graphene [44,45]. The addition of N 2 gas with Ar improved the thermal conductivity of the mixed plasma and increased the number of molecular ions [46]. The improved thermal and electrical conductivity of the nitrogen provided better nucleation conditions and, hence, more graphene layers were obtained.…”
Section: Resultsmentioning
confidence: 87%
“…Observation of N2 + (B 2 ∑u + →X 2 ∑g + ) transitions also indicates that N2 + is abundant [10]. Characteristic emissions and numerical calculations of species such as N2, N2 + , N + , and N in low-and atmospheric pressure of nitrogen luminescent (glow) discharges have been examined [11,12]. N2 and N2 + species in nitrogen plasma play vital role in synthesis of new functional and mechanical materials as they have strong chemical activity.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the research on low-pressure arc discharge fields concentrate on the gas discharge [7][8][9][10][11][12][13], the theoretical and experimental research on the gaseous form of alkali metal DC arc discharge are less reported. In this paper, the numerical and simulation modeling of lithium-vapor DC arc discharge in a low-pressure environment is studied.…”
Section: Introductionmentioning
confidence: 99%